An encyclopedia of practical translation and interpreting - Chan, Sin-wai (The Chinese University Press, 2018)
As a sequel to An Encyclopaedia of Translation: Chinese-English, English-Chinese published in 1995, this volume focuses on practical translation and interpreting, the two emerging areas of increasing importance in recent decades, and all chapters are fully illustrated with examples in translation between Chinese and English. Scholars and experts from China, France, Hong Kong, Spain, Taiwan, the UK, and the United States share their experiences in translation or interpreting practice. An Encyclopaedia of Practical Translation and Interpreting should be of great interest to both specialists and general readers.